A Device for Comprehensive Noninvasive Diagnostics of the Tissue Microcirculation System of Human Skin - Sidorov V. V. Viktor Vasiljevich; Rybakov Yu. L. Yury Leonidovich; Gukasov V. M. Vadim Mikhaylovich; Evtushenko G. S. Gennady Sergeevich (2021, 2021)
Title screen